TSPYL2 Is Important for G1 Checkpoint Maintenance upon DNA Damage - Tao, Kin Pong; Fong, Sze Wan; Lu, Zhihong; Ching, Yick Pang; Chan, Kin Wang; Chan, Siu Yuen (PLOS ONE, 2011)
Nucleosome assembly proteins play important roles in chromatin remodeling, which determines gene expression, cell proliferation and terminal differentiation. Testis specific protein, Y-encoded-like 2 (TSPYL2) is a nucleosome assembly protein expressed in neuronal precursors and mature neurons. Previous studies have shown that TSPYL2 binds cyclin B and inhibits cell proliferation in cultured cells suggesting a role in cell cycle regulation. To investigate the physiological significance of TSPYL2 in the control of cell cycle, we generated mice with targeted disruption of Tspyl2. These mutant mice appear grossly normal, have normal life span and do not exhibit increased tumor incidence. To define the role of TSPYL2 in DNA repair, checkpoint arrest and apoptosis, primary embryonic fibroblasts and thymocytes from Tspyl2 deficient mice were isolated and examined under unperturbed and stressed conditions. We show that mutant fibroblasts are impaired in G1 arrest under the situation of DNA damage induced by gamma irradiation. This is mainly attributed to the defective activation of p21 transcription despite proper p53 protein accumulation, suggesting that TSPYL2 is additionally required for p21 induction. TSPYL2 serves a biological role in maintaining the G1 checkpoint under stress condition.